Kompleksitas manajemen risiko di perbankan syariah: Identifikasi, pengukuran, dan strategi mitigasi - Zahro, Amellia (Maliki Interdisciplinary Journal, 2024)
Islamic banks act as both intermediaries and customer partners, safeguarding their interests through prudent practices and monotheistic beliefs. Every firm, especially Islamic banks, encounters business risks. In this situation, Islamic banks face more sophisticated risks than other businesses in the industry. This article examines approaches for risk management in Islamic banking. This sort of library research entails looking for and collecting books relevant to the research topic. Data analysis involves decreasing data, presenting data, and generating conclusions. Risk management in Islamic banking entails detecting, measuring, and controlling financing risks based on transaction features, financial conditions, collateral, and potential payment failures. Islamic banks incur several risks, including credit risks.There are two types of risks: benchmark risk and liquidity risk. Islamic banks must practice solid risk management in order to ensure the long-term viability and stability of their operations in a fast-rising market.